Pelaksanaan Pengelolaan Zakat Profesi di BMT Amanah Ummah Kartasura Tahun 2015 (Tinjauan Undang-Undang Nomor 23 Tahun 2011) - Akmal, Mizani; , Dr. M. Muhtarom, SH. MH (2017)
Zakat of profession is an obligation who must be done by every moslem and well managed by the 'āmīl zakāt institute. The other rule of Islamic law, the Indonesian Law Number 23 of 2011 on zakāt management is one foundation in order to build 'āmīl zakāt having legal status law in compiling and utilizing zakāt, infāq, and ṣadaqah. Based on such background, the researcher is interested to research and analysis how the practice of real management of zakāt of profession in BMT Amanah Ummah Kartasura based on valid laws. The purpose of this research is to know the perspective of the positive law toward realization of zakāt management especially in that of profession in BMT Amanah Ummah Kartasura. This research is a field reseach with qualitative approach. The methods in collecting data are interview, documentation, and observation. Data analysis use the deductive method. Based on the result of the study, the researcher concludes that the implementation of the management of zakāt profession in BMT Amanah Ummah Kartasura is in conformity with the Indonesian Law Number 23 of 2011 on the management of zakāt and the provisions of Islamic Shari'a because of its professionalisme in management and its distribution of zakāt has been right on target and has use the principle of justice.